Melawan Sunyi: Resistensi Identitas Perempuan dalam Novel Gadis Kretek - Intan Rosiana Devi; Wiyatmi (Jurnal Ragam Pengabdian, 2026)
This research begins with the issue of women's subordination within a patriarchal social structure that remains deeply rooted in Indonesian society. Ratih Kumala's novel Gadis Kretek presents female characters who demonstrate real resistance to the domination that silences their identities. This research aims to describe the forms of resistance to women's identities in the novel using the theoretical frameworks of Stuart Hall on representation and identity, Sara Mills on subject-object positions in discourse, and Simone de Beauvoir on existentialist feminism. The method used is descriptive qualitative. The data source is Ratih Kumala's novel Gadis Kretek. Data collection techniques were carried out through intensive reading, recording quotations, and data classification. Data analysis followed the Miles and Huberman model: data reduction, data presentation, and drawing conclusions. The results of the study show three forms of resistance: resistance to family, resistance to patriarchal culture, and resistance to domestic roles. The conclusion of this study confirms that the female characters in the novel represent an existential struggle to seize identity freedom amidst patriarchal power.